Identidad y futuro de los servicios sociales - Gutiérrez Resa, Antonio (Miscelánea Comillas, 2010)
In «Identity and Future of the Social Services» we start from the iden-tity gives it the useful values. Therefore we are analysing of the Social Services own values from the '60 years until present. Equally we compare the special values with the values of the joint society. The offered result showed us notable coincidences in the course of the 50 years. The final values and —to a lesser extent— instrumental values, with which social services are linked in the CCB (Christian community of assets) Plan (1960), hardly feature at all in the Con- certed Plan: the Community Social Services Plan for the whole of Spain agreed by the three administrations (1988). Eleven years after the Concerted Plan, new final values began to appear, while others were weakening because of a lack of instrumental values or benefits and facilities. There is currently a clear change of orientation in Community Social Services due to the appearance of emerging values which are underpinned by exchange values and permanent values. In thesame time, these values denote the double composition of the materialist andthe post materialist values.